Circulating immune complexes in steroid sensitive nephrotic syndrome - Bakkaloğlu, Ayşın; Saatçi, Ümit (The Turkish Journal of Pediatrics, 1982)
Non-complement-fixing immune complexes were detected by the EA (Fc) rosette inhibition test in the sera of patients with SSNS. The sera of fifteen patients with steroid sensitive nephrotic syndrome in relapse produced significantly greater Fc inhibition than the sera of 12 patients in remission.